2005
DOI: 10.1191/0267659105pf791oa
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary thromboendarterectomy for chronic thromboembolic pulmonary hypertension

Abstract: Hemodynamic improvement occurs immediately post operation. Mean pulmonary artery pressure decreased from 50 +/- 11 to 38 +/- 10 mmHg, pulmonary vascular resistance from 1246+482 to 515 +/- 294 dynes s/cm5 and cardiac index increased from 1.54 +/- 0.54 to 2.63 +/- 0.75 L/min per m2. Pump runs had an average duration of 187 +/- 29 min, circulatory arrest time was 29 +/- 11 min and crossclamp time 36 +/- 14 min. Extracorporeal membrane oxygenation can be an ultimate treatment for specific postoperative problems l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Only the most recent publications with the most complete data set from each institute were retained. As a result, 19 studies 6,15,21,22,25,26,29,30,33,35,36,38,40,[42][43][44][46][47][48] with a total number of 2729 patients were included for appraisal and data extraction ( Table 2).…”
Section: Quantity Of Evidencementioning
confidence: 99%
See 4 more Smart Citations
“…Only the most recent publications with the most complete data set from each institute were retained. As a result, 19 studies 6,15,21,22,25,26,29,30,33,35,36,38,40,[42][43][44][46][47][48] with a total number of 2729 patients were included for appraisal and data extraction ( Table 2).…”
Section: Quantity Of Evidencementioning
confidence: 99%
“…Four prospective studies were identified, 30,38,40,46) ; other studies were either clearly retrospective 6,15,22,25,29,35,42,44,47,48) or not specified. 21,26,33,43) Two studies presented results in a series of CTEPH patients treated surgically and medically 40,47) ; others included only series of surgically treated patients.…”
Section: Quality Of Evidencementioning
confidence: 99%
See 3 more Smart Citations